2015
DOI: 10.5327/z0100-0233-2015390100003
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos usuários atendidos no serviço de emergência em um hospital universitário em Pernambuco

Abstract: 13 Resumo Objetivo: Conhecer o perfil dos usuários atendidos na sala vermelha de um Hospital Universitário de Pernambuco. Métodos: Estudo descritivo, exploratório e quantitativo, realizado no setor do atendimento de emergência de um Hospital Universitário de Pernambuco, utilizando como fonte de dados o Livro de Registro dos atendimentos diários, coletados de janeiro a junho de 2013. Os dados foram organizados em uma planilha no programa Microsoft Office Excel ® 2010. Logo após, foram apresentados em gráfico e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
2
3
0
4
Order By: Relevance
“…In this case, corroborating with the study of Miranda and Sarti [29], which brings in total 51.4% of cases between the ages mentioned above, as well as other studies [30][31][32].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this case, corroborating with the study of Miranda and Sarti [29], which brings in total 51.4% of cases between the ages mentioned above, as well as other studies [30][31][32].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, about 61% of ingested alcoholic substances, corroborating with several studies [30,31,44]. However, the study of Franco et al, [45] diverges from this result stating that only about 45% of respondents claimed to have used alcohol.…”
Section: Discussionsupporting
confidence: 37%
“…17 The findings in this study are similar to results of previously published research, pointing out that the higher prevalence of deaths due to external causes is linked to the male population. 7,18 Such considerations also resemble international contexts, since, conducted in Mexico found that the highest mortality due to external causes was also among adolescents and young male adults in a given period. 19 Brazil has revealed the greatest inequality of mortality between men and women in external causes.…”
Section: Resultsmentioning
confidence: 94%
“…Nevertheless, research that sought to outline the profile of users of patients seen in the red room of a University Hospital showed that 66.0% of the assisted patients were male. 8 This divergence may be related to the type of care performed with greater prevalence in each institution, since the first receives mainly patients with clinical pathologies, while the second serves trauma victims.…”
Section: Discussionmentioning
confidence: 99%